Analisis Pendekatan Mimetik Pada Flim “Laura” Karya Hanung Bramantyo - Vanesa, Agiel (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This study aims to analyze the flim ”Laura” by Hanung Bramantyo which tells the story of the struggle of influencer Laura Anna after a tragic accident using a mimetic approach. Through this mimetic approach, it attempts to connect literary works with reality. The method used by the author in analyzing the flim “Laura” by Hanung Bramantyo is a qualitative descriptive method with a focus on observing dialogue in the flim to provide data that is in accordance with reality. The technique of collecting data and information uses the technique of listening and taking notes. The data source for this study comes from news and podcast concerning events experienced by Laura Anna. The author obtained 9 data that are in accordance with mimetic evidence from reality. The writer got mimetic evidence after the writer watched the flim “Laura” by Hanung Bramantyo repeatedly. Apart from that, the writer also tried to understand and study the flim as best as possible in order to get data that was in accordance with real events or in accordance with reality.